Effectiveness of Bangun-Bangun Leaf (Coleus Amboinicus Lour) on Breast Milk Production in Post Partum Mothers - Mendawaty Pandiangan; Lili Farlikhatun (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
The target of achieving exclusive breastfeeding is still difficult to achieve optimally due to several things including disruption or non-smooth milk expenditure. Data in Indonesia shows exclusive breastfeeding coverage is only 42%. Various efforts were made, one of which was by exploring the potential of bangun-bangun leaf herbs to increase breast milk production. The purpose of this study was to measure the effectiveness of the bangun-bangun leaf intervention on breast milk production. This research was quasy experimental design. The location used for this research is in the PMB Mendawaty working area in May - June 2023. The study sample was 32 post partum in which there were 16 control groups and 16 intervention groups giving bangun-bangun leaf extract. The bivariate analysis used is the Chi-Square test. The results of the chi-square analysis resulted in an odds ratio value (OR: 2.14; 95% Confident Interval 1.08 – 4.23; p value 0.033) it can be concluded that giving bangun-bangun leaf extract can increase breast milk production up to 2 times compared to not consuming bangun-bangun leaves and is statistically significant.